2012
DOI: 10.1007/s11033-012-2453-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of the plasma riboflavin levels and riboflavin transporter (C20orf54) gene statuses in Kazak esophageal squamous cell carcinoma patients

Abstract: To evaluate the association of the plasma riboflavin level in Kazak esophageal cancer patients and their riboflavin transporter (C20orf54) gene statuses. Plasma riboflavin levels were detected by high performance liquid chromatography in Kazak patients with esophageal squamous cell carcinoma (ESCC) and healthy controls. C20orf54 mRNA and protein expression were analyzed by real-time fluorogenic quantitative polymerase chain reaction and immunohistochemistry in samples from 61 ESCC patients consisting of both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Some findings suggested that riboflavin at high doses might promote lung cancer progression (Yang et al, 2013). Defective expression of C20orf54 gene statuses is associated with the development of esophageal squamous cell carcinoma and this may represent a mechanism underlying the decreased plasma riboflavin levels in ESCC (Ainiwaer et al, 2013). Decreased blood riboflavin levels are correlated with defective expression of RFT2 gene in gastric cancer (Eli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some findings suggested that riboflavin at high doses might promote lung cancer progression (Yang et al, 2013). Defective expression of C20orf54 gene statuses is associated with the development of esophageal squamous cell carcinoma and this may represent a mechanism underlying the decreased plasma riboflavin levels in ESCC (Ainiwaer et al, 2013). Decreased blood riboflavin levels are correlated with defective expression of RFT2 gene in gastric cancer (Eli et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the theoretical relationship between gene promoter hypermethylation as an epigenetic modification with the down regulation of gene transcription, we analyzed hRFT2, due to the down regulation of these genes in ESCC and GC (Maynur et al, 2012;Julaiti et al, 2012). Map CpG-rich islands within the hRFT2 regulatory region by professional software with bisulfate sequencing primers, which used to amplify the gene promoter region sequences that are spanning 3 kb around the transcription start site.…”
Section: Methylation Profiles Of the Hrft2 Gene In Sihamentioning
confidence: 99%
“…Decreased protein expression of hRFT2 is related to malignant progression both esophageal squamous cell carcinoma and gastric cancer (Pangrekar et al, 1993), due to the hRFT2 is responsible for transporting riboflavin and riboflavin deficiency has been reported as a risk factor for cancer. Relatively speaking that alter expression of hRFT2 is the most important factors contributing to transporting and absorption of riboflavin in the intestinal (Maynur et al, 2012), whereas the Riboflavin deficiency can cause a variety of metabolic problems that lead to skin and mucosal disorders (Julaiti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…C20orf54 has been identified as an ESCC susceptibility gene [ 7 ]; however, the expression of C20orf54 in ESCC is inconsistent. The gene is lower in ESCC tissues compared with normal tissues [ 10 ]. By contrast, Lu et al [ 11 ] showed that the C20orf54 protein level in ESCC tissues was significantly higher than that in adjacent normal tissues.…”
Section: Introductionmentioning
confidence: 99%